Financial Market Imperfections and Productivity Growth - Bruce C. Greenwald; Joseph E. Stiglitz (The Research Institute of Industrial Economics (IUI), 1989)
This paper examines the impact of financial market imperfections on long-term productivity growth. It focuses on failures in markets for the sale of equity securities and hence on the failure of markets which help firms diversify the risks of real investment. The paper examines separately situations in which productivity growth is driven by learning-by-doing and where it results from the cumulative impact of explicit investments in technology by firms. In general, a multiplicity of steady-state growth paths exists with different growth rates along each path. The particular path followed by any single economy (and hence the growth rate of that economy) will depend significantly on policy interventions which mitigate effects of financial markets.
Keywords: D20; G10; G32; 330; Financial markets; productivity growth; market failure; steady-state growth path